The Government of London : The struggle for reform - Rhodes, Gerald, 1926- (Book collections on Project MUSE., 1970)
Mr Rhodes describes the course of events from 1957 until 1965 when the new system came into operation in Greater London. He analyses the motives of the participants, including the political parties, the local authorities, government departments and professional bodies.